The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00122-018-3089-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of genomic regions influencing kernel zinc and iron in maize

Abstract: Key messageGenome-wide association study (GWAS) on 923 maize lines and validation in bi-parental populations identified significant genomic regions for kernel-Zinc and-Iron in maize.AbstractBio-fortification of maize with elevated Zinc (Zn) and Iron (Fe) holds considerable promise for alleviating under-nutrition among the world’s poor. Bio-fortification through molecular breeding could be an economical strategy for developing nutritious maize, and hence in this study, we adopted GWAS to identify markers associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
118
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 78 publications
7
118
0
Order By: Relevance
“…Hindu et al. () identified the significant genomic regions in maize for kernel Zn and Fe concentrations using GWAS on 923 maize lines, followed by validation in bi‐parental populations. GWAS identified 20 SNPs significantly associated with kernel Zn concentration, and 26 SNPs were significantly associated with Fe concentration.…”
Section: Strategies For Zn Biofortification Of Maizementioning
confidence: 99%
See 3 more Smart Citations
“…Hindu et al. () identified the significant genomic regions in maize for kernel Zn and Fe concentrations using GWAS on 923 maize lines, followed by validation in bi‐parental populations. GWAS identified 20 SNPs significantly associated with kernel Zn concentration, and 26 SNPs were significantly associated with Fe concentration.…”
Section: Strategies For Zn Biofortification Of Maizementioning
confidence: 99%
“…Subsequently, bi‐parental populations revealed that 11 SNPs for Zn and 11 SNPs for Fe have significant effects on the variance of these traits. These findings are very useful for mineral biofortification of maize and may also facilitate the cloning of important genes in the background of these traits (Hindu et al., ).…”
Section: Strategies For Zn Biofortification Of Maizementioning
confidence: 99%
See 2 more Smart Citations
“…These correlations are influenced by environmental and genetic factors and might be attributable to linkage or pleiotropic effects of genes. The genetic factors include several genes that encrypt metal transporter proteins in maize inbred lines, or the presence of common transporters for several minerals (Qin et al, 2012;Hindu et al, 2018). Quantitative trait loci (QTLs) for Fe and Zn in maize are present on the same chromosome arm, which suggests that simultaneous improvement of Fe and Zn contents is possible (Qin et al, 2012).…”
Section: Correlations Between Grain Iron and Zinc And Maize Yieldmentioning
confidence: 99%